The Effect of Digital Competence, Work Discipline, and Work Motivation on Employee Performance at the Regional Civil Service and Human Resource Development Agency (BKPSDM) of Kampar Regency - Aulia Rahma Dini; Kurniawaty Fitri; Prima Andreas Siregar (Journal of Management Economics and Financial Accounting, 2025)
This study aims to analyze the effects of digital competence, work discipline, and work motivation on employee performance at the Regional Civil Service and Human Resource Development Agency (BKPSDM) of Kampar Regency. The research problem focuses on the suboptimal level of employee performance amid increasing demands for public service quality and the growing use of digital technology, making an empirical investigation necessary to identify the determining factors and the most dominant variable influencing performance. This study employs a quantitative approach using a survey method. The research population includes all employees of BKPSDM Kampar Regency, with a total sample of 52 respondents selected using a census method. Data were collected through questionnaires that had been tested for validity and reliability, and were analyzed using multiple linear regression with the assistance of SPSS version 25. The results indicate that digital competence and work motivation have a positive and significant effect on employee performance, while work discipline has a positive but not statistically significant effect in partial testing. Simultaneously, the three independent variables significantly influence employee performance, with work motivation identified as the most dominant factor. These findings confirm that improving employee performance is not only dependent on digital technical competence but is also strongly influenced by work motivation, while work discipline functions as a supporting factor in task implementation. Therefore, efforts to enhance employee performance at BKPSDM Kampar Regency should focus on strengthening work motivation and continuously developing digital competence.